Determinants of feelings of anxiety in students entering the job market - Bożena Muchacka; Bogusław Dec (Institute of Social Affairs of the Pedagogical University of Cracow, 2023)
Work on the sense of anxiety among young people entering the labour market is scarce in the Polish literature. They usually concern a general approach to expectations, ambitions and related hopes for a good future. There is a lack of connectors showing the negative, psychological eff ects of entering a new stage of life, as well as the studies confirming (or denying) the existence of a correlation between the feelings of anxiety and the beginning of working life. The available publications related to the topic were written several or more years ago, in the days before the pandemic and the war in Ukraine, while the new reality completely changed the psyche of the young generation entering the stage of professional life. The most psychologically significant negative aspect of having to look for a job is the possibility of various mental disorders and problems. The most common consequences of failure in this area include anxiety, fear, stress and the associated uncertainty before the future. The results show that there are no statistically significant differences in the general level of anxiety related to entering the job market in male and female students. Students with general anxiety disorders also experience anxiety in the sphere of job search. The hypothesis that there is a negative corrlation between the level of self-efficacy over job search and the overall level of anxiety related to entering the job market was confirmed in the present study. The results obtained further indicate that there were no statistically significant differences in the overall level of anxiety related to entering the job market between those who begin their studies and those who complete them. Uwarunkowania poczucia lęku u studentów wkraczających na rynek pracy Prace nad poczuciem lęku wśród młodych osób wkraczających na rynek pracy są w polskim piśmiennictwie niedostateczne. Dotyczą zazwyczaj ogólnie ujmowanego podejścia do oczekiwań, ambicji i związanych z nimi nadziei na dobrą przyszłość. Brakuje łączników, ukazujących negatywne, psychiczne skutki wkraczania w nowy etap życia oraz badań potwierdzających (lub negujących) istnienie korelacji pomiędzy poczuciem lęku, a początkami życia zawodowego. Dostępne publikacje powiązane z tematem powstały kilka lub kilkanaście lat temu, w czasach przed pandemią i wojną na Ukrainie, podczas gdy nowa rzeczywistość zmieniła całkowicie psychikę młodego pokolenia rozpoczynającego etap życia zawodowego. Najistotniejszym z psychologicznego punktu widzenia negatywnym aspektem konieczności szukania pracy, jest możliwość wystąpienia różnorakich zaburzeń i problemów natury psychicznej. Do najczęstszych skutków niepowodzeń w tej dziedzinie zaliczyć możemy lęk, strach, stres oraz związaną z nimi niepewność przed przyszłością. Uzyskane wyniki badań wskazują na brak istotnych statystycznie różnic w ogólnym poziomie lęku związanym z wkraczaniem na rynek pracy u studentów i studentek. Studenci, u których pojawiają się ogólne zaburzenia lękowe odczuwają także lęk w sferze poszukiwania pracy. Hipoteza o ujemnej korelacji między poziomem poczucia własnej skuteczności nad poszukiwaniem pracy, a ogólnym poziomem lęku związanego z wkraczaniem na rynek pracy, znalazła potwierdzenie w niniejszych badaniach. Uzyskane wyniki wskazują ponadto na brak istotnych statystycznie różnic w ogólnym poziomie lęku związanym z wkraczaniem na rynek pracy pomiędzy osobami, które rozpoczynają studia, a osobami, które je kończą.